Bi2O3 and La10Si6O27 composite electrolyte for enhanced performance in solid oxide fuel cells. Issue 1 (March 2016) - Absah, H Q Hj Hairul; Bakar, M S Abu; Zaini, J Hj; Azad, A; Ming, L C
Abstract: Adding suitable metal oxide into lanthanum silicate apatite can produce a composite with a good oxygen ion-conducting electrolyte that enhances the performance of solid oxide fuel cells (SOFCs). In this paper we present the synthesis and characterisation of Bi2 O3 and La10 Si6 O27 composite prepared by a solid state reaction. The sintering temperature of the composite was 1500°C for 10 hours with the heating and cooling rates of 10°C per minute. The properties of the resulting composite have been characterised by X-ray diffraction (XRD), scanning electron microscopy (SEM), and ionic conductivity measured by an a.c. impedance spectroscopy (IS). Rietveld refinement of XRD data shows that the composition is purely the mixture of Bi2 O3 and La10 Si6 O27 with the unit cell parameters of the main phase as a = 9.9810 (8) and c = 7.3239 (6) Å. The room temperature crystal structure was hexagonal with space group P63 /m. The highest ionic conductivity of 1.76 × 10 -2 Scm -1 with a corresponding activation energy of 0.39 eV was obtained at 750°C. SEM images show the material is densed enough to use as an electrolyte for SOFCs.